Synthesis and Antifungal Activity of Some Bis-(2-arylimino-3-yl-thiazolidinones) and Bis-(1-aryl-3-yl-2-thiohydantions) derived from Hydroquinone - Rautela, R.; Joshi, P.C. (Asian Journal of Chemistry, 2010)
Some bis-(2-arylimino-3-yl-thiazolidin-4-ones) and bis-(1-aryl-3-yl-2-thiohydantoins) were synthesised from bis-(4-aryl-3-thiocarbamides) and screened for their antifungal activity against Aspergillus flavus, Helminthosporium tetramera and Pennicillium decombens.